2024
DOI: 10.1371/journal.pone.0297836
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bread diet on intestinal dysbiosis and irritable bowel syndrome symptoms in quiescent ulcerative colitis: A pilot study

Aleix Lluansí,
Marc Llirós,
Robert Carreras-Torres
et al.

Abstract: Gut microbiota may be involved in the presence of irritable bowel syndrome (IBS)-like symptomatology in ulcerative colitis (UC) patients in remission. Bread is an important source of dietary fiber, and a potential prebiotic. To assess the effect of a bread baked using traditional elaboration, in comparison with using modern elaboration procedures, in changing the gut microbiota and relieving IBS-like symptoms in patients with quiescent ulcerative colitis. Thirty-one UC patients in remission with IBS-like sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
1
1
0
Order By: Relevance
“…Likewise, the consistency in beta diversity, which measures the differences in microbial community composition between different samples, suggests that there were no changes in microbial composition across the interventions. These results are consistent with a similar trial conducted in subjects diagnosed with ulcerative colitis, which examined the effects of a two-month intervention with two different sourdough breads (differing in percentage) [43]. Consistent with our results, the above-mentioned study with 23 subjects reported no differences microbiota diversity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Likewise, the consistency in beta diversity, which measures the differences in microbial community composition between different samples, suggests that there were no changes in microbial composition across the interventions. These results are consistent with a similar trial conducted in subjects diagnosed with ulcerative colitis, which examined the effects of a two-month intervention with two different sourdough breads (differing in percentage) [43]. Consistent with our results, the above-mentioned study with 23 subjects reported no differences microbiota diversity.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our results, the above-mentioned study with 23 subjects reported no differences microbiota diversity. Furthermore, although the bread treatment suggestively reduced the Firmicutes/Bacteroidetes ratio, both groups experienced some relief from symptoms resembling intestinal bowel disease [43]. Likewise, a one-week clinical trial involving 20 healthy subjects that compared sourdough bread consumption to white bread found similar results, with no noticeable differences in alpha and beta diversity or relative abundances at the phylum level [44].…”
Section: Discussionmentioning
confidence: 86%